Peran Lingkungan Sekolah dalam Pembentukan Karakter Disiplin Siswa di Kelas XI SMA Dr. Soetomo Surabaya - Novitasari, Aldila; Zaman, Akhmad Qomaru; Lestari, Bernadetta Budi (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
This research is about the role of the school environment in the formation of student discipline in class XI SMA Dr. Soetomo. The purpose of this study was to determine the role and inhibiting factors of the school environment in the formation of the disciplinary character of Class XI SMA Dr. Soetomo.The type of research used is qualitative research, using data analysis with a Likert scale. The validity of the data was obtained by carrying out triangulation activities, namely technical triangulation and time triangulation.Based on the results of the study, it was revealed that the role of the school environment had a good role in the formation of the character of student discipline and limited time, facilities from the school, and also the background of the parents were included in the inhibiting factors of the role of the school environment in the formation of the character of student discipline in class XI SMA Dr. Soetomo.